Urban Welfare and Social Innovation in Italy - Lavinia Bifulco (Social Work and Society, 2019)
Social policies in Italy are today concerned at the same time by a drastic reduction in spending and the experimentation of new public action strategies, within a context shaped by re-centralization of budget constraints and effects of financialization and economic crisis, especially as for growing vulnerability and inequality. In this context, urban/local welfare is the main laboratory for social innovation, but it has to cope with increasing social problems through decreasing resources and powers, due to austerity measures and the strengthening of supranational control. Actually the theme of innovation has gained considerable space in public agendas, starting with the European one. Yet the picture that emerges from the research on its inclusive effects is far from univocal. Moreover, the discourses and the strategies centered on innovation have a very ambiguous relationship with dynamics of privatization and retrenchment of public welfare. Ambiguities, problems and opportunities involved in this scenario will be deepened mainly referring to interventions in disadvantaged neighborhoods.